2013
DOI: 10.1074/jbc.m112.446542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inducible Nitric-oxide Synthase Dimerization Inhibition by Novel Pyrimidine Imidazoles

Abstract: Background: Overproduction of nitric oxide by dimeric inducible nitric-oxide synthase (iNOS) is physiologically harmful. Results: Pyrimidine imidazole derivative (PID) binds to both the iNOS dimer and monomer causing irreversible monomerization and inhibition of dimerization, respectively. Conclusion: PID can physiologically inhibit iNOS both during and after its assembly into active enzyme. Significance: Our study reveals PID's dual ability to inhibit iNOS as well as their kinetic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Mechanistic studies (spectroscopy and competition binding) performed by Blasko et al later confirmed that pyrimidinylimidazoles do act by coordinating the heme center of iNOS monomers and allosterically blocking dimerization, and it was proposed that the observed selectivity reflects different dimer assembly kinetics in eNOS and nNOS (vs iNOS). It was shown more recently that pyrimidinylimidazoles can also break up active dimers into monomers in cells and that the monomer‐inhibitor complex is irreversible and cannot be converted back into active dimers by added l ‐Arg or H 4 B.…”
Section: Development Of Inos Inhibitorsmentioning
confidence: 99%
“…Mechanistic studies (spectroscopy and competition binding) performed by Blasko et al later confirmed that pyrimidinylimidazoles do act by coordinating the heme center of iNOS monomers and allosterically blocking dimerization, and it was proposed that the observed selectivity reflects different dimer assembly kinetics in eNOS and nNOS (vs iNOS). It was shown more recently that pyrimidinylimidazoles can also break up active dimers into monomers in cells and that the monomer‐inhibitor complex is irreversible and cannot be converted back into active dimers by added l ‐Arg or H 4 B.…”
Section: Development Of Inos Inhibitorsmentioning
confidence: 99%
“…Dimerization of iNOS is required for optimal enzymatic activity for which multiple cofactors including calmodulin, heme, FAD, NADPH, FMN and BH4 are important [13]. E. coli K1 interaction with human brain microvascular endothelial cells (HBMEC) induced biopterin levels, which in turn is responsible for increased production of NO [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibitors of iNOS dimerization have therapeutic potential in effectively controlling iNOS activity and reducing the high levels of NO produced under pathological conditions (29). Recently, pyrimidine imidazole derivatives were reported to be versatile iNOS inhibitors by interacting with both dimer and monomer entities of the iNOS enzyme (30). On the other hand, active compounds from nitrite assay may affect enzymatic activity by directly binding to the active enzyme site (substratebinding site).…”
Section: Discussionmentioning
confidence: 99%